Frequency of endo-globularhemotropic parasites in short haired sheep in Córdoba-Colombia - B, BERNARDO REYES; Ã, JOSÉ CARDONA; V, DONICER MONTES (The Indian Journal of Animal Sciences, 2020)
The infection caused by hemoparasites is one of the diseases of greater presentation within the tropical and subtropical countries in the world, anaplasmosis and babesiosis are diseases caused by intracellular hematropics that make up the complex of parasitic sadness. Hematropic agents (Anaplasma ovis, Anaplasma marginale, Trypanosoma vivax, Trypanosoma melophagium, Babesia ovis and Babesia motasi) are common cause of blood infections in sheep. A prospective descriptive type study was carried out. For convenience, a simple random probabilistic sampling type was used. 25 sheep farms were selected from small producers (who had 25 females and 1 male) representative of the department, who manage sheep as a production system. The technique of capillary microcentrifugation was used, where the percentage volume of blood cells was determined red blood cells (Hematocrit), by reading on a Hawksleymicrohaematocrit reader table, subsequently, they were made blood smears that were stained with WRIGTH dye and were evaluated under the light microscope. It can be concluded that the prevalence found in the study for Anaplasma (24.4%) and Babesia (18.4) in short hair sheep in the department of Córdoba, is not a significant valuebecause the agro-ecological conditions of this area are conducive to the development of specific vectors of these microorganisms, based on the results of the study, it is timely to implement prophylactic measures to reduce the incidence of these agents, because they are directly related to economic losses in the world sheep population, considerably deteriorating the health status of the animals and in some cases causing death.